Sahih al Boukhari: being the traditions of saying and doings of the prophet Muhammad as narrated by his companions - Imam Boukhari (Dar El Fiker, 1993)
tr, jil.1=c.1; sn,jl.2-5,c.1/tr, jil.7=c.1; jil.8=c.1-2; jil.9=c.1/tr, jil.1=c.2; jil.6=c.1